2018
DOI: 10.1080/14712598.2018.1425388
|View full text |Cite
|
Sign up to set email alerts
|

Alemtuzumab for the treatment of multiple sclerosis

Abstract: Alemtuzumab is a monoclonal antibody that targets for the destruction CD52+ cells, particularly B and T cells. Alemtuzumab is approved in more than 50 countries around the world for the treatment of adult patients with relapsing remitting multiple sclerosis (MS). Areas covered: In this review, the authors summarize biological, clinical and safety data related to the use of alemtuzumab in patients with MS. The authors then provide their expert opinion on alemtuzumab and the field as of whole before providing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 75 publications
3
23
0
Order By: Relevance
“…4b-d) to first investigate the immune cell depleting activity of a mouse αCD52 antibody that was previously reported to have biological effects 30 . Consistent with the clinical effects of alemtuzumab on circulating lymphocytes in humans 22,23 , the mouse αCD52 antibody efficiently depleted CD4 + and CD8 + T cells as well as CD19 + B cells in both the lung and spleen ( Supplementary Fig. 5).…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…4b-d) to first investigate the immune cell depleting activity of a mouse αCD52 antibody that was previously reported to have biological effects 30 . Consistent with the clinical effects of alemtuzumab on circulating lymphocytes in humans 22,23 , the mouse αCD52 antibody efficiently depleted CD4 + and CD8 + T cells as well as CD19 + B cells in both the lung and spleen ( Supplementary Fig. 5).…”
Section: Resultssupporting
confidence: 69%
“…By comparison, CD52 encodes a membrane glycoprotein present at varying levels on the surface of various leukocytes but not hematopoietic cells 21 . In addition, alemtuzumab is a monoclonal anti-CD52 (αCD52) antibody that results in preferential and prolonged depletion of circulating T and B cells 22,23 and is FDA approved for the treatment of B-cell chronic lymphocytic leukemia [24][25][26] and relapsing remitting multiple sclerosis [27][28][29] . Because of its biological role in immune cells relevant to asthma as well as its potential translational implications, we, therefore, prioritized CD52 as a strong causal positional candidate gene for functional validation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These findings not only point to a novel pathway for development of asthma but may also have potential translational implications. For example, we demonstrated that treatment of mice with an α CD52 antibody mimicked the immune cell-depleting activity of alemtuzumab in the circulation in humans 33,34 . We readily observed depletion of immune cells in spleen, which in mice is considered as accurately reflecting the pool of peripheral immune cells 64 .…”
Section: Discussionmentioning
confidence: 99%
“…By comparison, CD52 encodes a membrane glycoprotein present at high levels on the surface of various immune cells, including lymphocytes, monocytes, and dendritic cells. In addition, alemtuzumab is a monoclonal anti-CD52 (αCD52) antibody that results in preferential and prolonged depletion of circulating T and B cells 33,34 and is FDA approved for the treatment of relapsing remitting multiple sclerosis [35][36][37] and B-cell chronic lymphocytic leukemia [38][39][40] . Because of its biological role in immune cells relevant to asthma as well as its potential translational implications, we therefore prioritized CD52 as a strong causal positional candidate gene for functional validation (Fig.…”
Section: Enrichment Of Asthma-associated Variants In Regulatory Elemementioning
confidence: 99%
See 1 more Smart Citation